RANCANG BANGUN INSTRUMENTASI HALL EFFECT SENSOR MAGNETIC PADA DYNAMOMETER PRONY BREAKE DENGAN SISTEM MONITORING LCD 16X4 DISPLAYBERBASIS MIKROKONTROLER ARDUINO - Septian Dwi Kuncoro; Althesa Androva; Agus Mukhtar (Cross-border, 2023)
A dynamometer is a machine used to measure the torque (torque) and rotational speed (rpm) of the power produced by an engine, motor or other rotating drive. Dynamometers can also be used to determine the power and torque required to operate a machine. So the research aims to be able to design a prony brake dynamometer using a Hall Effect Magnetic Sensor. And can find out the performance of the Hall Effect Sensor and engine performance on the results of the value of Torque and Horse Power. As for the results of this study, it was found that the prony brake dynamometer using the hall effect sensor can work according to its function. And using the hall effect sensor in this system, the average reading result has an error of 1.42%, meaning that the sensor is suitable for use on a prony brake dynamometer machine because the error threshold is 2%.